Integrated math-reading method and pupil behavior and achievement in beginning reading - Jung, Ma. Aveline Averilla (2004)
This experimental study examined the relative effects of math-reading method on pupil achievement in beginning reading. Thirty four preschool learners were the subject of this study. The study revealed a significant difference in the achievement of the learners who were taught the math-reading method, and those taught the traditional phonics-sight method. The experimental group performed better than the control group. The results proved that young children's mathematical ability through the math-reading method could initiate better performance in beginning reading.